Analisis Pengaruh Brand Ambassador dan Harga pada Aplikasi Ruang Guru terhadap Minat Beli Konsumen pada SMAN 03 Jember - Husen Randi; Akhmad Suharto; Tatit Diansari Reskiputri (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aimed to determine and analyze the brand ambassador and the price of the Ruangguru application that had a significant effect on the buying interest of SMAN 03 Jember students. This type of research is explanatory research. The population in this study were all students of SMAN 03 Jember, totaling 1040. The sample used was 91 respondents using the purposive sampling technique. The analysis tool uses multiple linear regression. The study's results prove that the brand ambassador and price on the Ruangguru application significantly affect buying interest in SMAN 03 Jember students. Keywords: Brand Ambassador, Price, Buying Interest